2019
DOI: 10.30795/scijfootankle.2019.v13.955
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term follow-up after surgical treatment of fifth metatarsal base fractures in professional soccer players

Abstract: Objective: Fifth metatarsal fractures occur mainly in young athletes, with an estimated incidence of 1.8 per 1,000 people a year. The objective of this study was to evaluate the functional outcome of professional soccer players subjected to surgical treatment of fifth metatarsal base fractures. Methods: A total of 34 soccer players who underwent surgery from July 2001 to June 2016 were evaluated. All participants were evaluated by the American Orthopedic Foot and Ankle Score (AOFAS) and visual analogue scale (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…However, it should be taken into account that an efficient rehabilitation, without compromising the whole process of consolidation and recovery of the patient, reduces the risk of presenting refractures and the presence of pseudarthrosis. Among the studies reviewed, it was evidenced that the following variables were not influential factors for a favorable recovery: surgical time, healing time, Torg classification and if they use a graft during the surgical procedure (12)(13)(14).…”
Section: Image 1 Radiographs Of the Right Foot With Fracture Of The F...mentioning
confidence: 99%
“…However, it should be taken into account that an efficient rehabilitation, without compromising the whole process of consolidation and recovery of the patient, reduces the risk of presenting refractures and the presence of pseudarthrosis. Among the studies reviewed, it was evidenced that the following variables were not influential factors for a favorable recovery: surgical time, healing time, Torg classification and if they use a graft during the surgical procedure (12)(13)(14).…”
Section: Image 1 Radiographs Of the Right Foot With Fracture Of The F...mentioning
confidence: 99%
“…There is evidence from numerous studies that minimally invasive intramedullary screw fixation allows early postoperative weight-bearing, with union rates ranging from 89% to 100% and no need for bone-grafting 3,5,49,50,99,133,137,157-159 . The main disadvantages of intramedullary screws are a demanding insertion technique, the risk of irritation of the sural nerve, and symptomatic prominence of the screw head 3,5,49,122,130,133,158,160-163 .…”
Section: Principles Of Treatmentmentioning
confidence: 99%
“…Plate fixation has been successfully employed for Torg type-II and III fractures 176,178 . In cases of delayed healing or nonunion (Torg type-II and III fractures), several authors have combined internal fixation with the application of bone marrow aspirate concentrate (BMAC) to the fracture site 134,141,161,172,179 or cancellous bone-grafting from the calcaneus, the tibia, or the iliac crest 6,40,56,141,162,175,178-182 . Popovic et al found less refractures (0 versus 27%) in professional football players with Torg type-I and II fractures when 4.5-mm screw fixation was supplemented by local bone-grafting 40 .…”
Section: Principles Of Treatmentmentioning
confidence: 99%
See 2 more Smart Citations